Against 'Saving Lives': Equal Concern and Differential Impact. (1st July 2015) - Chappell, Richard Yetter
Abstract: Bioethicists often present 'saving lives' as a goal distinct from, and competing with, that of extending lives by as much as possible. I argue that this usage of the term is misleading, and provides unwarranted rhetorical support for neglecting the magnitudes of the harms and benefits at stake in medical allocation decisions, often to the detriment of the young. Equal concern for all persons requires weighting equal interests equally, but not all individuals have an equal interest in 'life‐saving' treatment.